The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00508-015-0881-9
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic and biochemical analysis of cardiac function and injury among female amateur runners post-marathon

Abstract: The data collected does not provide any solid evidence of pathological changes in the cardiac function of female amateur runners post-marathon, although the lab values indicate a strongly increased myocardial stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies have now reported that after marathon and ultramarathon running events, evidence of cardiac fatigue in the form of diastolic dysfunction is present in some runners (more often men than women) (12,36,37,43,54,55,57). However, this does not appear to be the case following most forms of aerobic exercise, and it seems fair to say there is no deficit in cardiovascular function for most exercisers after a single bout of aerobic or resistance exercise.…”
Section: Translation From the Laboratory To The Field: What Matters?mentioning
confidence: 99%
“…Several studies have now reported that after marathon and ultramarathon running events, evidence of cardiac fatigue in the form of diastolic dysfunction is present in some runners (more often men than women) (12,36,37,43,54,55,57). However, this does not appear to be the case following most forms of aerobic exercise, and it seems fair to say there is no deficit in cardiovascular function for most exercisers after a single bout of aerobic or resistance exercise.…”
Section: Translation From the Laboratory To The Field: What Matters?mentioning
confidence: 99%